Evaluación in vitro de la resistencia a la flexión de dos resinas compuestas nanohíbridas, OPALLIS de la FGM y NEOFIL de la Kerr - Sarango Guaillas, José Luis (2018)
In the development of dentistry; techniques and materials are being renewed steadily; as well as the properties of the materials in dentistry, the flexural resistance or modulus of rupture is one of the properties present in the composite resins; for this reason, the present investigation was to determine the flexural strength of two composite resins, the nanohibridas opallis (FGM) and of the Neofil (KERR). The sample was composed of 30 blocks of composite resin nanohibridas, 15 blocks of the Opallis resin (FGM) and 15 blocks of Neofil resin (KERR) in both cases in tone A3; prepared under specifications of ISO 4049, 25mm in length, 2mm thick and 2mm wide. We considered two groups, group A: 15 Opallis resin blocks and group B: 15 blocks of Neofil resin. Subsequently, to blocks of resin underwent a test of flexion of 3 points in a universal testing machine Marshall model, at a speed of 1,7mm/min. The data collected from the study of flexion were analyzed using the statistical test T-Student, thereby obtaining values of 115,759Mpa for group A (opallis) and values of 92,972Mpa for group B (Kerr), which gives us a statistically significant difference of 19.685% of flexural resistance to l group A. The data collected from the study of flexion were analyzed using the statistical test T-Student, thereby obtaining values of 115,759Mpa for group A (opallis) and values of 92,972Mpa for group B (Kerr), which gives us a statistically significant difference of 19.685% of flexural resistance to l group A. Keywords: Bending, light cured, hybrid, nanoparticles, nanorelleno